Pengembangan Kemampuan Berwirausaha Dalam Program Kerja Market Day Kkndik Unismuh Makassar - Ibrahim Rahman; Andika Safar; Saputra .; Sulvahrul Amin; Ariana .; Rismawati . (CV. ITTC INDONESIA, 2026)
The aims of the research is to find out how the MARKET DAY Work Program at SMPN 4 Mangarabombang helps develop students' entrepreneurial skills. The reason for this study is that students have not been getting enough knowledge about entrepreneurship, and there are not many activities that help them learn more about it. To collect information, the study uses observation, interviews, and reviewing documents. The findings show that students are excited to take part in Market Day and they start to understand what entrepreneurship is in a creative way. Also, the support from the school, including teachers and students, plays a big role in making the activity run smoothly.